PENGARUH BUDAYA KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PT BESAR INTAN GEMILANG TANGERANG SELATAN - Anisa Wardania; Suwanto (Jurnal Menara, 2026)
The purpose of this study is to determine the effect of Work Culture and Career Development on Employee Performance at PT Besar Intan Gemilang. This research employs a quantitative method with an associative descriptive approach. Data were collected through questionnaires and analyzed using descriptive test, classical assumption test, simple and multiple linear regression analyses, and hypothesis testing assisted by SPSS version 27. The results show that the Work Culture variable (X1) has a positive and significant effect on Employee Performance (Y), indicated by t-value asmuch 6.156 > 1.670 and a significance value of 0.000 < 0.05, means that H₀₁ is rejected and Ha₁ accepted. The Career Development variable (X2) does not have a significant partial effect on Employee Performance (Y), with a t-value of 1.122 < 1.670 and significance value of 0.266 > 0.05, meaning H₀₂ is accepted and Ha₂ rejected. Simultaneously, Work Culture (X1) and Career Development (X2) have a positive and significant effect on Employee Performance (Y), shown by an F-value of 19.145 > 3.15 and significance value of 0.000 < 0.05, these means that of H₀₃ and are acceptance of Ha₃. The coefficient of determination (R²) is 0.382 or 38%, indicating Work Culture and Career Development collectively contribute 38% to Employee Performance, while remaining 62% is influenced by other factors wich is not assessed on this research. Therefore, the regression models appered are valid have contributionts variables to Employee Performance at PT Besar Intan Gemilang, Tangerang Selatan.